Passenger preference analysis: light rail transit or bus versus car - Dell’Olio, Luigi; Ibeas, Angel; Dominguez, Alberto; Gonzalez, Felipe (Transport, 2012)
To begin with, his article studies the user’s preferences when faced with the introduction of two completely different public transport systems: the bus and the Light Rail Transit (LRT). Also, it examines how the modal distribution varies between the private car and each of the new systems, in particular. In addition, the most important variables for users when travelling in a congested corridor are individualized and a study is made on how these variables influence on the modal distribution. The results of the stated preferences of surveys are modelled using mixed logit models. Values are estimated for user’s time and the demand elasticity is determined with respect to the relevant variables. Different situations are created to analyse how user’s behaviour changes with the changes in the most important variables. Furthermore, this article quantifies the effects of the more relevant variables and shows that the LRT can attract more demand than a bus service, but it must guarantee a regular and frequent service, at the same time as charging competitive fares. It is also shown that for the introduction to be more successful any taken action should be accompanied by policies that chastise the use of the private car such as increased parking charges or higher fuel taxes. First Published Online: 19 Sep 2012